Aeromonas sobria cellulitis with septic shock: rare but potentially lethal in chronic liver disease - Pal, Dipankar; K., Rajiv Karthik (International Journal Of Community Medicine And Public Health, 2023)
Aeromonas, a common bacterial resident of freshwater is known to cause gastrointestinal illness in humans. Contaminated water and aquatic foods are the usual sources. Gastrointestinal disease is usually mild in normal individuals and responds to common antibiotics. However, extra-intestinal infections by Aeromonas species have been increasingly reported. Severe skin and soft tissue infection followed by septic shock may be seen in immunocompromised individuals. Bacteremia can also occur secondary to invasive gastroenteritis in persons with impaired immunity. Patients with decompensated chronic liver disease have been noted to be at especially high risk for fatal infection due to this pathogen. It can cause early bacteremia and rapid death without surgical debridement. We report a case of fatal Aeromonas cellulitis with septic shock in a patient with known advanced alcoholic liver disease. It started following minor skin injury and subsequent exposure to pond water. The patient presented late with septic shock and succumbed to his illness.